Cellulose nanomaterials in oil and gas industry and bio-manufacture: Current situation and future outlook - Qasim Allawi Bader; Zainab T. Al-Sharify; Jameel M. Dhabab; Haider Kamil Zaidan; Ahmed Mahdi Rheima; Duaa Mohammed Athair; Tomy Muringayil Joseph; Ehsan kianfar (Case Studies in Chemical and Environmental Engineering)
Recent advances in the production and use of cellulose nanoparticles are detailed in this review. Global demand for sustainability is on the rise, and fossil fuel use is also on the rise. Consequently, the oil and gas industry must maintain its focus on R&D of new, environmentally friendly technologies and materials. Oil and gas companies are interested in cellulose nanoparticles (CNMs) for several reasons, including their renewable potential, high specific surface area, adjustable surface chemistry, and good mechanical, barrier, thermal, and rheological characteristics. Oil and gas production will become more sustainable and environmentally friendly as a result of all this. There are many manufacturing procedures that may be used to manufacture materials with different structures and physicochemical qualities. Biomedicine, sensing, wastewater treatment, paper and cardboard manufacture, and the packaging sector are just a few of the many fields that benefit from cellulose nanomaterials (CNMs), especially cellulose nanofibers and cellulose nanocrystals. These materials have several desirable characteristics, such as being renewable, having a large surface area, being very stiff and strong under tension, and being very flexible on the surface because of hydroxyl groups. This has led to the scale production of these materials; for example, several companies currently make cellulose nanoparticles in quantities of several tons per day. The remarkable properties of nano-cellulose biopolymers, which may be produced by a wide range of microbes and plant materials, including rice husks, tea leaves, and other agricultural byproducts, have recently attracted more attention due to the development of nanotechnology. Scientists use a range of methods, including chemical, mechanical, and enzymatic processes, to synthesize cellulose nanoparticles from food scraps. Nanomaterials' primary characteristics are defined by their surface functionalization, extraction source, and extraction processes. In this article, we will examine their present production rates and their applications in several areas, including as healthcare, sustainable construction materials, and energy storage and generation. Our focus will be on recent developments and upcoming trends in the production and use of cellulose nanoparticles. The purpose of this article is to provide a synopsis of what is known about cellulose and its technical biological uses, including its ability to heal wounds, transport drugs, construct tissues, and regenerate bones. The most recent findings from both basic and applied research are contained in a comprehensive bibliography. Materials derived from cellulose may be modified to possess the specific physical, mechanical, and chemical characteristics needed for use in the biomedical field. It doesn't take much work to alter cellulose's chemical structure and conjugate it with other materials, including nanoparticles. Because of this, the applications are straightforward to form and process, inexpensive, biodegradable, and biocompatible.